2013
DOI: 10.4161/psb.24575
|View full text |Cite
|
Sign up to set email alerts
|

Tomato (Solanum lycopersicum) Homologs of TRIPTYCHON (SlTRY) and GLABRA3 (SlGL3) are involved in anthocyanin accumulation

Abstract: In Arabidopsis thaliana the CPC-like MYB transcription factors [CAPRICE (CPC), TRIPTYCHON (TRY), ENHANCER OF TRY AND CPC 1, 2, 3/CPC-LIKE MYB 3 (ETC1, ETC2, ETC3/CPL3), TRICHOMELESS 1, 2/CPC-LIKE MYB 4 (TCL1, TCL2/CPL4)] and the bHLH transcription factors [GLABRA3 (GL3) and ENHANCER OF GLABRA 3 (EGL3)] are central regulators of trichome initiation and root-hair differentiation. By transforming the tomato orthologous genes SlTRY (TRY) and SlGL3 (GL3) into Arabidopsis, we demonstrated that SlTRY inhibited tricho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 17 publications
(19 reference statements)
1
26
0
Order By: Relevance
“…Phylogenic analysis suggested that SlTRY and CPC originated from a single common ancestor [33] . SlTRY was shown to function quite similarly to the Arabidopsis CPC , including in the formation of ectopic root-hairs, in the induction of a no-trichome phenotype and in its action as a repressor of anthocyanin accumulation in Arabidopsis [34] . In summary, SlTRY functions in a similar way as CPC for the epidermal cell differentiation and the anthocyanin accumulation in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phylogenic analysis suggested that SlTRY and CPC originated from a single common ancestor [33] . SlTRY was shown to function quite similarly to the Arabidopsis CPC , including in the formation of ectopic root-hairs, in the induction of a no-trichome phenotype and in its action as a repressor of anthocyanin accumulation in Arabidopsis [34] . In summary, SlTRY functions in a similar way as CPC for the epidermal cell differentiation and the anthocyanin accumulation in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that tomato and Arabidopsis use similar transcription factors for root-hair and trichome cell differentiation and that the SlTRY -like R3 MYB may be a key common regulator of plant root-hair and trichome development [33] . In prior work, we also analyzed the anthocyanin content of SlTRY and SlGL3 transgenic Arabidopsis [34] . We showed that anthocyanin accumulation was repressed in the CPC::SlTRY and GL3::SlGL3 transgenic Arabidopsis plants, suggesting that the tomato genes of SlTRY and SlGL3 are involved in anthocyanin biosynthesis [34] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another bHLH TF (PIF3), directly binds with the promoters of genes involved in the biosynthesis of anthocyanin and act as a positive component in PHYA-mediated anthocyanin biosynthesis [50]. In tomato, bHLH TF gene SlGL3 is also not participating in the putative MBW protein complex in tomato as is the case in Arabidopsis [51]. In maize, several bHLH TFs were identified to induce tissue-specific anthocyanin biosynthesis, such as Lc, R, B, Sn and Hopi genes [52].…”
Section: Discussionmentioning
confidence: 99%
“…16 SlTRY had similar functions to CPC including root-hair induction, inhibition of trichome formation and anthocyanin accumulation in Arabidopsis. 16,17 On the other hand, SlGL3 did not show any observable GL3-like functions in Arabidopsis. 16,17 To evaluate evolutionary relationships among anthocyanin synthesis-related transcription factors, we performed phylogenetic analyses (Fig.…”
mentioning
confidence: 81%